2015
DOI: 10.1515/jcim-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of gas discharge visualization to measure massage therapy outcomes

Abstract: Background The purpose of this study was to evaluate the short-term effects of massage therapy using gas discharge visualization (GDV), a computerized biophysical electrophoton capture (EPC), in tandem with traditional self-report measures to evaluate the use of GDV measurement to assess the bioenergetic whole-person effects of massage therapy. Methods This study used a single treatment group, pre–post-repeated measures design with a sample of 23 healthy adults. This study utilized a single 50-min full-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Some of these have produced repeatable effects with results that conform to biofield healing expectations: for example, the devices using gas discharge visualization based on the Kirlian effect. [61][62][63][64] Nonetheless, the continued rejection of Kirlian photography by conventional science shows how difficult it is to get such novel instruments accepted. This generates another major barrier regarding biofield healing, leading critics to dismiss the topic as purely "subjective.…”
Section: Objectivitymentioning
confidence: 99%
“…Some of these have produced repeatable effects with results that conform to biofield healing expectations: for example, the devices using gas discharge visualization based on the Kirlian effect. [61][62][63][64] Nonetheless, the continued rejection of Kirlian photography by conventional science shows how difficult it is to get such novel instruments accepted. This generates another major barrier regarding biofield healing, leading critics to dismiss the topic as purely "subjective.…”
Section: Objectivitymentioning
confidence: 99%
“…In energy medicine, the word "energy" does not refer to energy as physicists commonly use it, but rather to a felt sense that therapists describe as energetic-like, magnetic-like, or tingling-like sensations in or around the body. Experimental and anecdotal reports demonstrate that physical measures correlate with these feelings, e.g., electromagnetic and magnetic fields [1,2], mechanical vibrations [3], and other less conventional approaches [4]. However, there is currently no reliable detection method to assess when the presumed energy is present.…”
Section: Introductionmentioning
confidence: 99%
“…An independent meta-analysis of randomized controlled trials (RCTs) addressing pain concluded that massage effectively reduced pain compared to sham and active comparators, and improved mood and health-related quality of life compared to active comparators, and concluded that massage is a viable pain management option [45]. A limited number of massage studies have shown results on PTSD, but many studies have demonstrated results on related symptoms such as anxiety, stress, and depression [40,42,46-48].…”
Section: Introductionmentioning
confidence: 99%